Current Status and Future Perspective on Enzyme Involving in Biocontrol of Plant Pathogen - Ami Chaudhari; Jesal Patel (International Journal for Research in Applied Sciences and Biotechnology, 2021)
To sustain the quality and abundance of fruit, feed and fiber provided by farmers all over the world, plant diseases must be regulated. Plant diseases may be prevented, mitigated, or regulated using a variety of methods. Growers also rely on chemical fertilizers and pesticides for good agronomic and horticultural practices. Such agricultural inputs have taken a vital part in spectacular increases in crop yield and quality over the last 100 years. Microbial enzymes function as biocatalysts for key biochemical reactions and also assist microbes reproduce in a particular niche. The ability of rhizosphere microorganism to increase the growth of plant and control phytopathogens has long been known. Rhizosphere microbes may aid plants in several ways in their fight against phytopathogens. Of all recognized biocontrol pathways, the excretion of lytic enzymes is known as an important way to prevent phytopathogens from living in the region of the rhizosphere. Rhizosphere microorganism produces chitinases, cellulases, proteases, and glucanases in reaction to phytopathogen assault. For assessing antagonist-pathogen interactions, ecological characteristics of antagonists in the rhizosphere, and optimizing the effectiveness of bacterial, fungal, and viral biocontrol agents, new molecular approaches have become available. Given the experience of fungicides in near future, biological management would be another method to control diseases of plant. Since agro-ecosystem is a flexible and functioning structure that involves many variables that affect disease and production of crop, other IPM methods to control diseases of crop are also important in different surrounding conditions. As result, to successfully minimize disease production and crop yield loss in various crop systems, other IPM management mechanisms other than biological control should be considered and implemented.